A Computational and Theoretical Review on the Motion of a Spinning Spherical Particle in Media with Different Viscosities - Braga, F. L.; Pauli, I. G.; Amorim, V. S. (Journal of Applied Nonlinear Dynamics, 2026)
Ballistic calculations were the first attempt where computers were used for, and the oblique launching of objects when studied at an ideal approach is quite simple with a parabolic trajectory of particles. The same motion could become intrinsically difficult to solve when dissipative forces are considered at the model. The present work shows a brief theoretical review on the motion of a spinning spherical particle under the influence of the gravitational field, the drag force and the Magnus effect. The drag forces can alter the translation speed and the angular velocity. We determined the profiles of the trajectories, velocity field and the modifications of frequency in two scenarios, first when the particle is moving across one medium and second when it pass through one medium to another. The results, trajectories obtained are in agreement the predictions for the cases where non continuous and non uniform forces are acting on a body.